Pengaruh Kualitas Produk dan Kepercayaan Merek Terhadap Minat Beli Produk Lipstik Wardah di Kecamatan Buleleng - Dewi, Dyani Puspita; Yulianthini, Ni Nyoman (Jurnal Pendidikan Ekonomi Undiksha, 2021)
This study aimed to examine the influence of product quality and brand trust both simultaneously and partially on the buying interest in Wardah Lipstick products in Buleleng District. The research design used was causal quantitative research. Determination of the sample in this study used purposive sampling technique. The number of samples used was 100 respondents. The instrument used in data collection was a questionnaire and the data analysis technique used was multiple linear regression analysis. The results of this study are: (1) Product quality and brand trust have a significant effect on buying interest in Wardah Lipstick products. (2) Product quality has a positive and significant effect on buying interest in Wardah Lipstick products. (3) Brand trust has a positive and significant effect on buying interest in Wardah Lipstick products